Asbab Al-Nuzul fi Mandur Nurcholish Madjid Al-Indunisiy - Zaky Mumtaz Ali (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2021)
This article aims to study the views of Nurcholish Madjid in the concept of Asbab Al-Nuzul and how these views have influenced his deals with the Holy Qur’an. The researcher adopted the method of induction and analysis to study this topic, where the researcher collected the writings of Nurcholish Madjid related to the causes of revelation, and then analyzed these writings to get out of them with the expected results. Among the most important of his writings on the causes of revelation is his article